Case Report: A case of cervical spinal epidural abscess combined with cervical paravertebral soft tissue abscess - Cao, Jun; Fang, Jincheng; Shao, Xuefei; Shen, Jun; Jiang, Xiaochun (Frontiers in Surgery, 2022)
Background: Spinal epidural abscess (SEA) is a rare purulent infection of the central nervous system. Abscesses confined to the spinal canal can compress the spinal cord, causing nerve damage and even death in severe cases[1]. Prompt diagnosis and treatment can relieve symptoms and prevent complications. To increase awareness of this rare disease, we report a case of a 58-year-old man with a cervical spinal epidural abscess combined with a soft tissue abscess in the neck and describe its clinical course, imaging feature, pathology, treatment, and patient prognosis. Case Description: A 58-year-old male patient was admitted to our hospital because of neck pain for 2 months, which worsened for 4 days. On the third day of admission, the muscle strength of the limbs decreased, and MRI of the spinal cord showed abnormal signal shadows in the spinal canal at the C1-C7 level and in the surrounding soft tissue on the right side of spine, suggesting the possibility of inflammatory lesions with local abscess formation. We immediately performed decompression of the spinal canal on the patient and performed incision and drainage of the cervical abscess. During the operation, we found a large amount of pus in the epidural space of the spinal canal, and there was a fistula between the cervical abscess and the epidural abscess of the spinal canal. The patient underwent continuous drainage and anti-infective treatment with sensitive antibiotics after operation. No recurrence of the abscess was observed and the patient recovered well. Conclusion: Early diagnosis is the key to the treatment of SEA, so radiologists and neurosurgeons need to strengthen their understanding of this rare disease to avoid misdiagnosis. For SEA with definite diagnosis, decompression surgery should be performed in a timely manner when symptoms of nerve compression occur, continuous drainage should be performed after surgery, and sensitive antibiotics should be used for anti-infective treatment.